SUNDANESE LANGUAGE INTERFERENCE IN PRONOUNCING ENGLISH FRICATIVE AND AFFRICATE CONSONANTS - Mohammad Soni (EEAL Journal (English Education and Applied Linguistics Journal), 2018)
This study investigated the Sundanese language interference in pronouncing English fricative and affricate consonants and the cause of errors in pronouncing them. This was conducted to 5 students in the 2nd year of Senior High School 1 Garut. The writer used qualitative method and case study design to analyze the research problems. Reading aloud test and interview were used to find out Sundanese language interference and the cause of errors. The language interference found was phonological interference; substitution and re-interpretation and there were seven reasons as the cause of errors. Finally, it is very necessary for the students to know how to pronounce English sounds that have different manner with the mother tongue, Sundanese.Keywords: Sundanese language interference, cause of pronouncing errors.